Endovascular Management of Cerebral Aneurysm: The Recent Trends - Gupta, Vipul; Londhe, Shrikant; Parthasarathy, Rajsrinivas; Ganaie, Hilal Ahmad (Indian Journal of Neurosurgery, 2018)
Cerebral aneurysm rupture is the leading cause of mortality and morbidity in patients with hemorrhagic stroke. Surgical clipping and endovascular coiling are the mainstay of management for securing the aneurysm. After International Subarachnoid Aneurysm Trial (ISAT) and Barrow Ruptured Aneurysm Trial (BRAT) results, worldwide trend has shifted gradually in favor of endovascular management. Nonetheless, endovascular management was faced with some limitations, especially while treating giant, wide neck bifurcation, blister, and small uncoilable aneurysm. The recent introduction of new devices such as flow diverter stents, microstents, bifurcation devices, double-lumen balloon catheters, and microcoils have proved to be effective in overcoming the limitations of traditional aneurysm coiling. The authors present a review of recent advances in the endovascular management of cerebral aneurysm.
Keywords: cerebral aneurysm; coiling; flow diverter